The elucidation of Dioscorea hispida's role in Molecular Oxidative Damage-mediated Toxicity in liver of meternal rats / Abdul Rahim Azlan - Azlan, Abdul Rahim (2016)
Dioscorea hispida, or "Ubi Gadung", has been studied widely in ethnobotany, ethnomedicine, nutritional sources, toxic content, structure and metabolism process and process of removing toxic content. This yam contains highly toxic alkaloid known as dioscorine, and other toxic substances such as cyanide. These toxic contents have shown pathogenic effect to human. The yam is believed can induce oxidative stress which leads to DNA damage. This study is conducted by using ROS assay and comet assay. The results show the DNA damage is directly proportional to D. hispida concentration. The toxicity of D. hispida has potential to induce genotoxicity.